(untitled) (The Research of Medical Science Review, 2024)
Cancer is significant public health issue across the world and cause huge morbidity and mortality across the world. It remains a huge well-being challenge around the world with many people analyzed every year. Changes to the genes that regulate our cells' growth and division are the primary cause of cancer, a hereditary disease. With billions of cells making up the human body, cancer may begin practically anywhere in the body. New cells replace old ones when they die because of aging or injury. This controlled mechanism can occasionally fail to function, causing damaged or aberrant cells to divide and expand when they shouldn't. Female breast cancer has surpassed lung cancer as the most commonly diagnosed cancer, with an estimated 2.3 million new cases (11.7%), followed by lung (11.4%), colorectal (10.0 %), prostate (7.3%), and stomach (5.6%) cancers. Shaukat Khanum Memorial Cancer Hospital and Research Centre is a tertiary care, nonprofit, charity cancer clinic. 22,745 new patients were enrolled for cancer treatment in 2020–21 at the Shaukat Khanum Memorial Cancer Hospital and Research Centre.